2024
DOI: 10.1200/po.23.00466
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Testing Utilization: Discrepancies Between Somatic and Germline Results in Patients With Cancer Reviewed at the UW Health Precision Medicine Molecular Tumor Board

Isaac P. Horn,
Anna L. Zakas,
Kelcy J. Smith-Simmer
et al.

Abstract: PURPOSE Somatic and germline testing are increasingly used to estimate risks for patients with cancer. Although both germline testing and somatic testing can identify genetic variants that could change a patient's care and eligible treatments, the aims of these tests and their technologies are fundamentally different and cannot be used interchangeably. This study examines the timing and results of somatic and germline genetic testing for patients with cancer at UW Health. METHODS Eight hundred and seventy-seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In the article that accompanies this editorial, Horn et al 15 present the experience of an academic health care center, the UW Health Precision Medicine Molecular Tumor Board, regarding the discrepancies between germline and somatic variants identified in their patients with advanced cancer. They found that only 50% of their patients who were eligible for germline analysis based on current guidelines received germline testing following tumor sequencing in their institution.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the article that accompanies this editorial, Horn et al 15 present the experience of an academic health care center, the UW Health Precision Medicine Molecular Tumor Board, regarding the discrepancies between germline and somatic variants identified in their patients with advanced cancer. They found that only 50% of their patients who were eligible for germline analysis based on current guidelines received germline testing following tumor sequencing in their institution.…”
mentioning
confidence: 99%
“…The study by Horn et al 15 also highlights how critical the timing of germline analysis can be for the clinical management of patients with advanced cancer. Many patients in their study cohort only received germline testing after developing advanced disease and following tumor sequencing, although they were eligible for germline evaluation based on their cancer type and age at onset at the time of diagnosis.…”
mentioning
confidence: 99%